PERBANDINGAN HUKUM KEPAILITAN ANTAR NEGARA INDONESIA DAN MALAYSIA DALAM SYARAT PERMOHONAN PAILIT TERHADAP SUATU PERUSAHAAN ASURANSI(Studi kasus perkara nomor: 45/PDT.SUS.PAILIT/2020/PN.NIAGA.JKT.PST) - Dimas Abimanyu Sasono (2022)
COMPARISON OF INSOLVENCY LAW BETWEEN INDONESIAN AND MALAYSIAN COUNTRIES IN TERMS OF BANKRUPTCY APPLICATION AGAINST AN INSURANCE COMPANY (Case Study Number: 45/Pdt.Sus.Pailit/2020/PN.Niaga.Jkt.Pst) Siti Rokayah Master of Law Study Program at the University of National Development "Veteran" Jakarta Dabimanyu9@gmail.com ABSTRACT Basically, insolvency is defined as a general confiscation that confiscates all assets of debtors for the benefit of their creditors. There is a weakness regarding the requirements of an insolvency application with the non-regulation of important definitions in the field of insolvency resulting in misconceptions or multi-interpretations in practice. Then the ease of applying for bankruptcy without looking at the state of a company's financial condition can be seen in the case of PT. AIA FINANCIAL's application for bankruptcy statement Against PT. AIA FINANCIAL was filed by MITRA KERJA on AIA insurance as well as being one of its creditors. There is a problem related to the legal comparison between the State of Indonesia and the State of Malaysia and how the Panel of Judges in passing the decision of Case Number: 45 / Pdt.SusPailit / 2020 / PN. Niaga.Jkt.Pst, whether it is in accordance with the terms and conditions of the bankruptcy request regulated in Law No. 37 of 2004 concerning Insolvency and Postponement of Debt Payment Obligations of the Republic of Indonesia. in principle the Insolvency Law of the two countries of Indonesia and Malayasia almost resembles however, the insolvency regulated by the State of Malaysia further clarifies the state of the debtor as for example: distinguishing legal subjects whether individuals or legal entities with the legal division scheme of the Insolvency Act 1967 for individual debtors and the Companies Act 2016 for corporate debtors. Then the terms of the application for bankruptcy are undeniable that the terms and certainties of the state of malayasia greatly clarify the existence of debts we can see in the law section 2 of the Insolvency Act 1967 the existence of a minimum amount of debt amended from RM30,000 (thirty thousand Malaysian ringgit) to RM 50,000 (fifty thousand Malaysian ringgit) which is a comparison of Indonesia's Insolvency Law. Indonesian Insolvency Law Law No. 37 of 2004 article 2 paragraph (1) does not clarify the minimum amount of debt as a condition of application. Keywords: Terms of Insolvency Application, Insurance Company